Zeolite‐Encaged Single‐Atom Rhodium Catalysts: Highly‐Efficient Hydrogen Generation and Shape‐Selective Tandem Hydrogenation of Nitroarenes - Sun, Qiming; Wang, Ning; Zhang, Tianjun; Bai, Risheng; Mayoral, Alvaro; Zhang, Peng; Zhang, Qinghong; Terasaki, Osamu; Yu, Jihong (Angewandte Chemie International Edition, 2019)
Single‐atom catalysts are emerging as a new frontier in heterogeneous catalysis because of their maximum atom utilization efficiency, but they usually suffer from inferior stability. Herein, we synthesized single‐atom Rh catalysts embedded in MFI‐type zeolites under hydrothermal conditions and subsequent ligand‐protected direct H2 reduction. Cs‐corrected scanning transmission electron microscopy and extended X‐ray absorption analyses revealed that single Rh atoms were encapsulated within 5‐membered rings and stabilized by zeolite framework oxygen atoms. The resultant catalysts exhibited excellent H2 generation rates from ammonia borane (AB) hydrolysis, up to 699 min−1 at 298 K, representing the top level among heterogeneous catalysts for AB hydrolysis. The catalysts also showed superior catalytic performance in shape‐selective tandem hydrogenation of various nitroarenes by coupling with AB hydrolysis, giving >99 % yield of corresponding amine products. Together alone: Single Rh atoms were encapsulated within MFI zeolites under in situ hydrothermal conditions and a ligand‐protected direct H2 reduction. The catalyst gave a high turnover frequency of 699 molH2 (molRh)−1 min−1 at 298 K for ammonia borane (AB) hydrolysis and exhibited superior catalytic efficiency in shape‐selective tandem hydrogenation of nitroarenes by coupling with the hydrolysis of AB.